Compensation policies across EU countries: Insights from SES data - Suleman, F.; Duarte, H.; Suleman, A. (GESIS 6th European User Conference for EU-Microdata, 2019)
The classification of countries based on socioeconomic differences has received particular attention in the context of comparative political economy. The literature of varieties of capitalism has contributed to our understanding of firms’ practices in different economic and institutional contexts and consequently has offered a categorisation of countries on the basis of those practices. In such a context, some literature examines how firms respond to labour market regulations and design human resources (HR) policies and practices. This stream focuses on comparative human resource management and clusters countries according to practices of managing people. Our research contributes to this literature and examines pay practices of firms across European countries. The goal of this study is classify firms according to their compensation policies within clusters of countries. It uses the Structure of Earnings Survey (SES2014) data to examine compensation policies of medium and large sized firms’ plants in five categories of countries, notably Liberal (United Kingdom), Nordic (Norway and Sweden), Central Europe (Belgium, France, Germany and Netherlands), Eastern Europe (Bulgary, Czech Republic, Hungary, Latvia, Lithuania, Poland, Romenia and Slovakia) and Latin (Italy, Spain and Portugal). It should be noted that the data of SES are collected at establishment level; we therefore use establishment as a proxy of firm. We apply a fuzzy cluster analysis to depict a picture of segmentation of plants according to the pattern of their compensation policies. Fuzzy cluster analysis is performed to deal with the expected overlapping of these policies. Secondly we performed Tobit regression analysis to evaluate the relationship between the clusters and the groups of countries and sectors of activity. Empirical findings pointed to four clusters, which we labelled as Internal Labour Markets (ILM), Qualification Pay (QFP), Market-based (MKT), and Individualised (IND) models in all countries according to their closeness to a theoretical model. The former is characterised by low dispersion, closeness to the market and industry mean wage; QFP, is associated with average dispersion and a high correlation with ISCO classification; MKT is observed a reward of specific skills through wage-tenure profile and a high differentiation comparatively to market and industry average wages; finally rules associated with individualised pay rules push firms into IND model and a accentuated dispersion. It includes differentiation within jobs, and between jobs associated with occupational category, evidencing a high vertical dispersion. However, the results show that compensation policies are fuzzy and the plants in each country present differences between sectors of activity. The ILM is the most representative cluster being more present in Nordic and with some expression in the Central Europe countries evidencing a low dispersion and low differentiation toward the market. We infer that the regulation of the markets and general coordination by the governments and unions explain this findings. Conversely the IND and MKT are more present in UK and transitional economies of Eastern Europe. This can result from the tension lived in the last years of the old paradigms of centralized economies and the liberal tendencies that influence some of these economies. At the same time it is observable for a lower dispersion and higher recognition of Qualifications on Public Administration and a clear association of the MKT cluster with the Financial sector independent of the group of countries.